Analisis Frekuensi Domain Pada Sinyal EEG Terhadap Stimulus Gambar Kemasan Produk: Studi Neuromarketing dalam Kemasan Produk - Suhendro, Jauzaa Maylia; Ni Wayan Nanik Suaryani Taro Putri; Endria, Felysia; Renanda Putra Prasetya, Gede (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2025)
Product packaging not only serves as protection but also functions as a strategic visual element that shapes consumer perception at the point of sale. With the advancement of neuroscience-based marketing, neuromarketing has emerged as a promising approach to investigate brain responses to visual stimuli. This study aims to analyze alpha wave activity in response to product packaging images categorized as attractive and unattractive. A total of 25 participants were involved, with visual stimuli selected based on a prior survey of 60 respondents. Brain activity was recorded using EEG from channels O1 and O2 and analyzed using the Power Spectral Density (PSD) method. The results indicate that attractive packaging elicited higher alpha wave activity compared to unattractive packaging and baseline, suggesting increased visual attention. Furthermore, PSD features were classified using three machine learning algorithms: Random Forest, Support Vector Machine, and K-Nearest Neighbors. Among them, Random Forest achieved the highest test accuracy at 78%. This study contributes to the objective evaluation of product packaging design through brain signal analysis and supports the development of data-driven marketing strategies.